EFFECT OF SOME ARTIFICIAL AND ALCOHOLIC SWEETENERS ON LIPID PROFILE AND BLOOD SUGAR IN GROWING RATS - M. Ayed; Basmaa S. Sheet; Omer Fawzi Abdulaziz (Mesopotamia Journal of Agriculture)
This study was designed to determine the impact of some artificial and alcoholicsweeteners (sucralose, T1, rebaudioside-A, T2 , xylitol ,T3 , and sorbitol, T4) on the level of some lipids and blood sugar in growing rats. The results showed a significant positive effect at (p≤0.05) on total cholesterol (TC) in serum in rats given sorbitol (T4) and xylitol (T3) which were 22.67 and 24.83 mg /dl respectively, compared with blank control (T *) and sucrose control (T0) (32.67 and 30.17 mg /dl). No significant decrease was noticed in triglycerides (TG) and very low density lipoprotein (VLDL) values in T4, T3, T2 and T1 treatments (40.83 and 8.17, 41.33 and 8.27, 47.33 and 9.47 and 48.50 and 9.75 mg/dl respectively), compared with T *(61.66 and 12.33) and T0 (52.50 and 10.50 mg /dl). A significant decrease in blood sugar in the rats given sucralose, rebaudioside-A , xylitol and sorbitol (97.00, 103.83 , 119.00 and 119.17 mg /dl respectively), while in blank control (T *) and sucrose control (T0) blood sugar found to be 129.83 and 143.00 mg/dl respectively. It was concluded that the artificial and alcoholic sweeteners, which used, play a positive role in reducing the level of blood lipids and blood sugar in rats.